A Guideline for development of construction price indices in Thailand: Residential construction price index - Thongthong, Ph.D., Tanit; Wacharawitoon, Apirak (Engineering and Applied Science Research, 2013)
This research presents a guideline for developing construction price indices as tools that reflect the changes of construction cost over time. In this paper, data of residential houses, townhouses and commercial shop-houses constructed in Bangkok and viscinity are collected for producing the indices : Input index, Output price index and Seller’s price index. To develop the construction price indices in Thailand, the system of data collection and analysis for different types of construction must be set up and the regulations to force the contractors and developers to provide construction cost information must be implemented.